Don't open your eyes : a novel - Constantine, Liv; Constantine, Liv (Bantam, 2025)
"In this twisted psychological thriller from the New York Times bestselling co-author of the Reese's Book Club Pick The Last Mrs. Parrish, a woman is tormented by nightmarish visions of her future - and then they start to come true"-- Provided by publisher.